Shared mechanisms in stemness and carcinogenesis: lessons from oncogenic viruses - Iacovides, Demetris; Michael, Stella; Achilleos, Charis; Strati, Katerina (Frontiers in Cellular and Infection Microbiology, 2013)
A rise in technologies for epigenetic reprogramming of cells to pluripotency, highlights the potential of understanding and manipulating cellular plasticity in unprecedented ways. Increasing evidence points to shared mechanisms between cellular reprogramming and the carcinogenic process, with the emerging possibility to harness these parallels in future therapeutics. In this review, we present a synopsis of recent work from oncogenic viruses which contributes to this body of knowledge, establishing a nexus between infection, cancer, and stemness.